Vidiškių šnektos deminutyvai - Markevičienė, Žaneta; Markevičius, Aurimas (Kalbotyra, 2005)
Diminutives are used abundantly in the subdialect of Vidiškiai, like in all the East Aukštaitian dialects. Therefore, it is not easy to explain why the subdialect of the Vidiškiai surroundings as well as the Širvintiškiai dialect in general are devoid of diminutival forms of hydronyms, and why the diminutival suffix -(i)ukas is totally absent in the writings of Konstantinas Sirvydas, who was a native of a region close to the Vidiškiai settlement. It should be mentioned that the said suffix presently has extreme popularity in the region. Although the older native speakers of the Vidiškiai subdialect tend to use numerous diminutival forms, the diminutive word-formation of their speech lacks diversity. Only seven suffixes are popular: -elis/-elė; -ėlis/-ėlė; -(i)ukas; -ytė; -(i)utė; -(i)okas/-(i)okė and -(i)otė. Diminutive nouns of the feminine gender are more numerous in their usage; therefore, some of the masculine suffixes have two corresponding “partners” of the feminine gender. E.g., the masculine suffix -(i)ukas is coupled with the feminine gender suffixes -ytė and -(i)utė; e.g. beȓn̑ù.kus ir ̮meȓgì.tæ ‘a little boy and a little girl’, pet̑ȓù.kus ir ̮kat̑ȓù.tæ ‘Pete and Cathie’. Shift of grammatical gender adds special tenderness to the diminutive forms, e. g.: val̑dunì.tæ ‘Dear Valdas’ instead of val̑dù.kus; stæpù.kus ‘Dear Stephanie’ instead of stæfù.tæ, etc. Some diminutives, especially those with the Slavic suffix -ka, have the meaning of familiarity.